THE EFFECTIVENESS OF TECHNOLOGY INTEGRATION IN LEARNING ON IMPROVING CRITICAL THINKING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS: Efektivitas Integrasi Teknologi dalam Pembelajaran terhadap Peningkatan Kemampuan Berpikir Kritis Siswa Sekolah Menengah Pertama - Pramesty Regita Cahyani; Suhartono; Ahmad Sodikin (SOSIOEDUKASI, 2025)
This study aims to determine the influence of the use of technology in learning on the critical thinking skills of students in grade IX.3 SMP Negeri 01 Belitang Mulya and describe the level of students' critical thinking skills after the application of technology-based learning. The research uses a quantitative approach with an associative type of research. Data were collected through a closed questionnaire spread and analyzed using simple linear regression. The results of the study showed that the use of technology had a positive effect on students' critical thinking skills, as evidenced by a significance value of 0.215 (> 0.05) so that the alternative hypothesis (Ha) was accepted. The level of students' critical thinking skills also increased from an average of 0.20 (low category) to 0.60 (medium category) after the integration of technology in learning. These findings confirm that technology can be an effective means of encouraging students' analytical, logical, and reflective thinking skills.